An integrated 45 L pilot microbial fuel cell system at a full-scale wastewater treatment plant. (October 2016) - Hiegemann, Heinz; Herzer, Daniel; Nettmann, Edith; Lübken, Manfred; Schulte, Patrick; Schmelz, Karl-Georg; Gredigk-Hoffmann, Sylvia; Wichern, Marc
Graphical abstract: Highlights: A 45 L MFC system was integrated into a large full-scale WWTP. Stable power output was obtained at extremely low COD concentrations of <130 mg/L. Power density positively correlated with wastewater temperature and conductivity. NERCOD and CE negatively correlated with COD influent concentrations. Full-scale MFC integration into WWTP would notable reduce overall energy demand. Abstract: A 45-L pilot MFC system, consisting of four single-chamber membraneless MFCs, was integrated into a full-scale wastewater treatment plant (WWTP) and operated under practical conditions with the effluent of the primary clarifier for nine months to identify an optimal operational strategy for stable power output and maximum substrate based energy recovery (Normalized Energy Recovery, NER). Best results with the MFC were obtained at a hydraulic retention time of 22 h with COD, TSS and nitrogen removal of 24%, 40% and 28%, respectively. Mean NER of 0.36 kWhel /kgCOD, deg and coulombic efficiency of 24.8% were reached. Experimental results were used to set up the first described energy balance for a whole WWTP with an integrated MFC system. Energetic calculations of the model WWTP showed that energy savings due to reduced excess sludge production and energy gain of the MFC are significantly higher than the loss of energy due to reduced biogas production.